Analysis Of Length Of Stay Decrease Of Sc Patients With Eracs Protocol - Nurhayati, Intan; Nadjib, Mardiati (Journals of Ners Community, 2022)
A clinical pathway (CP) is a concept of integrated service planning, based on medical service standards, care standards, and evidence with measurable results, medical care that is sick at home. Summarize each step given to the patient based on other service standards for the worker. Specified period CP is a standard of care that begins with evaluation, diagnosis, information support, rehabilitation, and clinical audit. Enhanced Post-Surgery Recovery (ERACS) is a multimodal designed to provide immediate recovery for post-surgery patients by preserving preoperative organ function and reducing stress responses during surgery. Perioperative treatment protocol. The most important keys to this protocol are preoperative counseling, nutritional optimization, standard anesthetic and analgesic use, and early mobilization. Enhanced recovery after surgery (ERAS) is a philosophy of perioperative care that has been applied in other settings since the 1990s, but in obstetrics in the form of enhanced recovery (ERACS) after cesarean section surgery. The application of was recently discovered. The ERACS Protocol aims to increase patient satisfaction, shorten patient stay and reduce costs. The ERACS protocol includes pre-hospital, preoperative, intraoperative to postoperative perioperative preparation and involves an interdisciplinary team of anesthesiologists, surgeons, nurses and nutritionists